Pengaruh Strategis Kyai dalam Mendukung Kemenangan PKB pada Pemilu Legislatif 2024 di Kendal - Ariya Maulana (Mahesa Research Center, 2024)
This study examines the role of Kyai in the political strategy of the National Awakening Party (PKB) in Kendal Regency, focusing on the combination of traditional pesantren-based approaches and the utilization of digital social media. While the involvement of religious leaders in Indonesian politics has been widely researched, there is limited exploration of the influence of Kyai's moral authority, pesantren community networks, and digital technology in garnering political support. The research employs a qualitative case study method, involving in-depth interviews with Kyai, PKB administrators, and voters and direct observation of campaign activities. Findings reveal that Kyai plays a significant role in mobilizing political support through their moral authority and emotional connection with the community. Meanwhile, PKB effectively utilizes social media to reach younger voters. This